Uptake of research-based recommendations to increase the impacts of Egypt’s national cash transfer program on the very poor - CGIAR Research Program on Policies, Institutions, and Markets (2020)
In response to research-based recommendations, Egypt’s Ministry of Social Solidarity made several changes to the Takaful and Karama cash transfer program: the targeting methodology was adjusted to reach more beneficiaries, the public communications around the program was improved, and expanded collaboration with other ministries turned Takaful and Karama into the centre-piece of a new national social protection system.